Holistic Trauma Healing After Earthquake In Islamic Boarding School: A Case Study Of Al-Bahjah Cianjur - Donny Fajar Ramadhan; Ajat Sudarjat; Khusni Mubarok; Gusrie Efendi (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2025)
Earthquakes can occur anywhere, anytime, and affect anyone. One of them is Islamic boarding schools known as Pondok Pesantren. They are known as institutions that focus on providing educational services to students. But how do they deal with earthquake disasters? This research aims to understand the impact of the earthquake disaster in the form of trauma for students and recovery efforts in the Islamic boarding school environment. The research started with collecting secondary data about Islamic boarding schools. Next is the primary data collection stage, through in-depth interviews with Islamic boarding school managers and Islamic boarding school students who are earthquake survivors. The interviews focused on their experiences during and after the earthquake and the efforts made by the Islamic boarding school management to carry out trauma healing. The research results concluded that holistic trauma healing carried out at the Al Bahjah Cianjur Islamic boarding school was an integration of spiritual and recreational trauma healing. Holistic trauma healing activities have succeeded in overcoming earthquake trauma, both short and long term. This activity provided new enthusiasm for the students so that the post-earthquake trauma recovery process could run more quickly.